Slum Spatial Planning Concept Seen from the Sympathy of the Community of Batu Bara Regency - Akus Harmoko; Abdiyanto; Cut Nuraini; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2024)
This research evaluates the irregularities in slum spatial planning, both housing and the lack of initial foundation facilities and infrastructure in Tanjung Tiram Village, Batu Bara Regency. One of the reasons is the high and uneven population density, especially in terms of land availability. The impact of this condition is poor environmental sanitation, which has the potential to affect environmental sustainability. Low public knowledge and understanding of sanitation can be seen in environmentally unfriendly behavior. One basic example is a lack of awareness of preserving rivers, which can be useful for daily life as a source of clean water due to the high rate of waste disposal into rivers, which can increase the risk of disease spread. The Batu Bara Regency Government is trying to improve the situation with the concept of slum spatial planning through community empowerment programs. The programmed is not running optimally due to a lack of community sympathy for the environment. Therefore, this research aims to examine the extent of community sympathy for the concept of spatial planning with the environmental sanitation improvement programmed in Tanjung Tiram Village, as well as the components that influence this sympathy. The research method used is qualitative with a rationalistic approach. The research began with a literature analysis to understand the research variables. Then, research was carried out in the field to describe the specifications of community sympathy in sanitation management, identify patterns of change in community behavior, and analyze the components that influence community sympathy. The findings show that community sympathy is reflected in responsibility and attention to the interests of others. The community is involved in the entire sanitation improvement process, from initiation to monitoring the use of bathing, washing, and toilets (MCK++). Community motivation comes from cadre intervention, which provides understanding, increases sympathy and responsibility, and strengthens community foundations in sanitation management. In this research, it is hoped that there will be increased cooperation and outreach to the community regarding the importance of slum spatial planning through community empowerment programmed by managing healthy environmental sanitation, developing integrated planning, and social supervision in implementing sustainable activity programmed.